2003
DOI: 10.1177/0038038503037002002
|View full text |Cite
|
Sign up to set email alerts
|

Disability and Bodies as Bearers of Value

Abstract: This paper considers the relevance of Pierre Bourdieu's conceptions of the body to the development of disability theory. We begin by discussing the limitations of reductive conceptions of disability. In so doing, we consider how far Bourdieu's (1990) concept of habitus offers a way of bringing an analysis of the body to bear upon an understanding of the social inequalities which are core to the lives of disabled people. Through focus groups with disabled people, the paper explores aspects of disabled people's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
112
2
16

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 17 publications
2
112
2
16
Order By: Relevance
“…This process of invalidation of the bodies and lives of disabled people (Edwards and Imrie 2003), also paves the way for institutionalized disablsm and abuse of clients (Oliver 1984, Barnes 1992, Jenkins and Davies 2006 which ultimately involves the denial of human rights (Scullion 2008b). The term 'abuse' is used to embrace the concept 'maltreatment' which has been defined as harm via health providers, with or without intention (Hassouneh-Phillips et al 2005).…”
Section: Invalidation and Abusementioning
confidence: 99%
“…This process of invalidation of the bodies and lives of disabled people (Edwards and Imrie 2003), also paves the way for institutionalized disablsm and abuse of clients (Oliver 1984, Barnes 1992, Jenkins and Davies 2006 which ultimately involves the denial of human rights (Scullion 2008b). The term 'abuse' is used to embrace the concept 'maltreatment' which has been defined as harm via health providers, with or without intention (Hassouneh-Phillips et al 2005).…”
Section: Invalidation and Abusementioning
confidence: 99%
“…Capital can have either material (e.g., economic) or immaterial forms (e.g., symbolic or social), which can be transformed into power at different rates of conversion (11). Physical ability is a frequently unacknowledged form of capital that is required in a world that has been constructed to suit those with able bodies (12). Habitus refers to the dispositions and tendencies that agents in a particular field acquire over time, and that provide them with the tools to compete in the fields they occupy (9).…”
mentioning
confidence: 99%
“…assim, para vencer a inércia corporal na partida, ganha (12) , que refere para velocistas portugueses valores de sJ e CmJ de 40.4 6.6cm e 43.8 7.0cm, respectivamente, e melhores marcas pessoais médias aos 100m de 11.14 0.25s, assim como pela análise da posição relativa ocupada pelos atletas da presente amostra nos respectivos rankings, poder-se-á classificar esta como sendo de elevado nível nacional.…”
Section: Pratical Applicationsunclassified
“…Weight transfer (Wt), or weight shift, is a coaching expression used to describe the motion of the centre of pressure, or the distribution between the feet of the 3 components of the ground reaction force during the golf swing. several authors found statistically significant differences between different skill level golfers (from professional to high handicap) when analysing the Wt between swings (5,12,18,27) . besides, Gatt et al (12) , Koenig et al (18) , Wallace et al (31) and Williams and Cavanagh (32) , while studying the Wt, found significant differences between golfers when using different shoes (metal spikes or soft spikes).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation